PENGARUH AVERAGE COLLECTION PERIOD, INVENTORY TURNOVER IN DAYS, AVERAGE PAYMENT PERIOD, DEBT RATIO, STRUKTUR ASET DAN UKURAN PERUSAHAAN TERHADAP PROFITABILITAS PERUSAHAAN (STUDI PADA PERUSAHAAN MANUFAKTUR SEKTOR INDUSTRI BARANG KONSUMSI YANG TERDAFTAR DI - Chermian Eforis; Gracella Pioleta (Ultima Management : Jurnal Ilmu Manajemen, 2019)
Company profitability is the company's ability to generate net income from its operational activities by managing all of its resources during an accounting period. Company profitability can be measured using Return on Assets (ROA). Return on Assets (ROA) is profitability ratio that shows how effective and efficient a company in managing its assets to generate net income. The purpose of this study is to obtain empirical evidence about the effect of some variables independent toward Return on Assets. Variables independent in this research are Average Collection Period, Inventory Turnover in Days, Average Payment Period, Debt Ratio, Asset Structure and Firm Size. The population in this study are consumer goods industry companies that are listed on the Indonesia Stock Exchange (IDX) during the period 2014-2018. Sampling is done by using purposive sampling method which the secondary data are analyzed using multiple regression method. The number of samples that fulfill sample criteria set by researcher are 25 companies. The results of this study are (1) Average Collection Period has no significant effect toward company profitability, (2) Inventory Turnover in Days has no significant effect toward company profitability, (3) Average Payment Period has positive significant effect toward company profitability, (4) Debt Ratio has no significant effect toward company profitability, (5) Asset Structure has no significant effect toward company profitability, (6) Firm size has positive significant effect toward company profitability